2003
DOI: 10.1097/00008469-200302000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol, diet, dentition and sexual practices in the epidemiology of oral cancer in Poland

Abstract: The effect of smoking, drinking, diet, dental care and sexual habits on the risk of oral and pharyngeal cancer was investigated in a case-control study conducted in Warsaw, Poland. The study comprised 122 patients (including 44 females) aged 23-80 years with histologically confirmed cancer of oral cavity and pharynx. Controls were 124 subjects (including 52 females) admitted to the hospital for different non-neoplastic conditions unrelated to tobacco and alcohol consumption, with frequency matched to cases by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
3
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 27 publications
13
123
3
8
Order By: Relevance
“…10 No association was seen between complete dental prosthesis and oral cancer, corroborating other studies. 8,11,12 On the other hand, high association of frequent gum bleeding during toothbrushing and oral cancer was found. Maier et al 12 reported among oral cancer cases that 40.9% had 3 mm or more dental calculus or tartar and 28% had chronic gingival infl ammation, thus indicating that patients with oral cancer could have poorer oral care and health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 No association was seen between complete dental prosthesis and oral cancer, corroborating other studies. 8,11,12 On the other hand, high association of frequent gum bleeding during toothbrushing and oral cancer was found. Maier et al 12 reported among oral cancer cases that 40.9% had 3 mm or more dental calculus or tartar and 28% had chronic gingival infl ammation, thus indicating that patients with oral cancer could have poorer oral care and health.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding is similar to that found in studies in Germany 12 and Poland. 11 Those who have frequent dental visits are generally more careful about their oral hygiene, and this behavior could be considered an indicator of good oral care, which can help eliminate or prevent mucosa exposure to certain carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…A diet rich in fruits and vegetables has been shown to reduce the risk of OSCC, in patients with and without a history of tobacco and/or alcohol abuse [6,[15][16][17][18][19][20][21][22].…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…A food frequency questionnaire was used to examine weekly consumption of several foods, including, milk, yoghurt, bread, pasta or rice, maize dishes, meat, fish, ham and salami and sausage, egg, cheese, potatoes, raw green vegetables and salads, cruciferae (broccoli, cabbage and brussel sprouts), carrots, fresh tomatoes, pulses, fresh fruit juice, apples or pears, citrus fruit, bananas, cakes and desserts. Dietary findings from the largest participating centres have been reported (Italy, 21 India, 22 Cuba, 23 Spain 24 and Poland 25 ).…”
Section: Risk Factor Assessmentmentioning
confidence: 99%